Bridge expansion joint anchoring area concrete with high crack resistance as well as preparation method and application thereof

By using high-temperature calcined diatomaceous earth-rice husk ash and modified rubber particle fibers in the concrete in the anchor area of ​​the bridge expansion joint, the problems of easy cracking, damage and poor durability of concrete are solved, the mechanical and crack resistance are improved, and the mechanical and crack resistance is extended. service life and reduce maintenance costs.

CN119263711APending Publication Date: 2025-01-07CCCC HIGHWAY BRIDGES NATIONAL ENGINEERING RESEARCH CENTRE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411323399.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The concrete in the anchorage area of ​​the bridge expansion joint is prone to cracking, breaking, and has poor durability, making it difficult to meet the requirements of impact resistance, ductility and crack resistance. Traditional materials have poor economicality and redundant performance indicators.

Method used

Using diatomaceous earth-rice husk ash after high temperature calcination as a high-active internal curing agent, modified rubber particles and modified polyacrylonitrile PAN fibers, the high crack resistance bridge expansion joint anchorage concrete is prepared through mixing and stirring to improve the concrete mechanical properties and crack resistance.

Benefits of technology

It significantly improves the mechanical properties and crack resistance of the concrete in the anchoring area of ​​the expansion joint, extends the service life, reduces maintenance costs, and achieves efficient crack resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263711A_ABST
    Figure CN119263711A_ABST
Patent Text Reader

Abstract

The invention discloses high-crack-resistance bridge expansion joint anchoring area concrete as well as a preparation method and application thereof. The method comprises the following steps: weighing the following raw materials in parts by weight: 650 to 660 parts of cement, 200 to 210 parts of fly ash, 100 to 110 parts of slag powder, 100 to 110 parts of a high-activity internal curing agent, 500 to 550 parts of sand, 500 to 550 parts of stone, 18 to 20 parts of rubber powder, 50 to 60 parts of modified rubber particles, 1 to 1.2 parts of a water reducing agent, 60 to 70 parts of steel fibers, 8 to 9 parts of modified PAN fibers and 230 to 240 parts of water; cement, fly ash, slag powder, a high-activity internal curing agent, sand, stone, rubber powder, modified rubber particles, a water reducing agent and water are mixed and stirred, and a concrete mixture is obtained; and adding the steel fibers and the modified PAN fibers into the concrete mixture, and continuously stirring uniformly to obtain the high-crack-resistance bridge expansion joint anchoring area concrete. The diatomite-rice hull ash after high-temperature calcination is adopted as the high-activity internal curing agent, the modified rubber particles and the modified PAN fibers of the concrete, so that the problems that the concrete in the anchoring area of the expansion joint is easy to crack and damage, poor in durability and the like are well solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of concrete materials, and more specifically to a bridge expansion joint anchorage zone concrete with high crack resistance, and a preparation method and application thereof. Background Art

[0002] As an important component of bridge expansion joints, the concrete in the anchorage area of ​​bridge expansion joints is often the easiest to damage and has the highest maintenance rate, which directly affects the operating status and service life of bridge expansion joints.

[0003] After the bridge is built and opened to traffic, the actual vehicle axle load is often much greater than the designed axle load. In addition, the increasing traffic volume on the road has led to a more obvious impact of vehicles on the expansion joints of the bridge. The huge impact force of vehicle tires on the expansion joint device of the bridge can cause the expansion joint components to be damaged, fall off or loosen, while increasing the damage to the concrete in the anchoring area and the expansion joint device of the bridge, greatly shortening its service life.

[0004] In the expansion joint anchorage area, due to factors such as temperature changes and load effects, higher requirements are placed on the impact resistance, ductility, durability and crack resistance of concrete.

[0005] Traditional concrete materials are difficult to meet these requirements. Shrinkage-compensating steel fiber concrete is usually used in engineering to improve its crack resistance, but it has poor toughness, is prone to cracking and shattering, and has incomplete performance indicators. There are also reinforcement solutions using high-performance materials such as UHPC, but they are less economical, have excessive redundancy in performance indicators, and are not conducive to promotion and replacement of expansion joint devices in the later stage.

[0006] Therefore, it is necessary to develop a new type of highly crack-resistant concrete for the anchorage area of ​​bridge expansion joints. Summary of the invention

[0007] In view of this, the present disclosure provides a highly crack-resistant concrete for a bridge expansion joint anchorage zone, and a preparation method and application thereof, to solve the problems of easy cracking, breakage, and poor durability of the concrete in the expansion joint anchorage zone.

[0008] According to one aspect of the present disclosure, a method for preparing concrete in the anchoring area of ​​a bridge expansion joint with high crack resistance is provided, comprising:

[0009] S1: weigh the raw materials according to the following weight parts: 650-660 parts of cement, 200-210 parts of fly ash, 100-110 parts of slag powder, 100-110 parts of high-activity internal curing agent, 500-550 parts of sand, 500-550 parts of stone, 18-20 parts of rubber powder, 50-60 parts of modified rubber particles, 1-1.2 parts of water reducing agent, 60-70 parts of steel fiber, 8-9 parts of modified polyacrylonitrile PAN fiber and 230-240 parts of water;

[0010] S2: Mixing and stirring cement, fly ash, slag powder, high-activity internal curing agent, sand, stone, rubber powder, modified rubber particles, water reducing agent and water to obtain a concrete mixture;

[0011] S3: adding steel fiber and modified polyacrylonitrile (PAN) fiber into the concrete mixture and continuing to stir evenly to obtain highly crack-resistant concrete for the anchorage area of ​​the bridge expansion joint.

[0012] In the above scheme, the high-activity internal curing agent described in step S1 adopts diatomaceous earth-rice husk ash after high-temperature calcination, wherein rice husk ash is a high-activity admixture. After being mixed with diatomaceous earth and calcined at high temperature, the respective advantages of the two materials can be brought into play in concrete. The high activity of rice husk ash improves the compactness of the internal structure of the concrete in the expansion joint anchoring area and improves the durability of the concrete. The porous structure of the diatomaceous earth after calcination absorbs and returns water, reduces the water loss caused by the hydration reaction in the internal pores of the concrete structure, reduces the shrinkage deformation of the expansion joint concrete, and reduces the risk of cracking of the concrete in the expansion joint anchoring area.

[0013] In the above scheme, the high-activity internal curing agent described in step S1 is prepared by the following method: crushing and grinding natural diatomaceous earth to a particle size range of 0.075~0.15mm, calcining at a high temperature of 800~820℃ for 55~65min, taking out after calcination and directly placing it in a low-temperature environment of -18~-22℃ for cooling for 50~70min; then mixing the cooled diatomaceous earth and rice husk ash in a mass ratio of 3:1, stirring at a high speed, calcining at 600~620℃ for 55~65min, and restoring to room temperature in a dry environment after calcination to obtain a high-activity internal curing agent.

[0014] In the above scheme, the high-temperature calcination time of 800~820℃ is 58min, 60min or 62min; the cooling in the low-temperature environment is cooling for 55min, 60min or 65min in a low-temperature environment of -18℃, -20℃ or -22℃; the high-temperature calcination time of 600~620℃ is 58min, 60min or 62min.

[0015] In the above scheme, the modified rubber particles described in step S1 are prepared by the following method: selecting broken rubber particles with a particle size of 1-3 mm, soaking the rubber particles in a 35% sodium hydroxide solution for 3.5-4.5 hours, and continuously stirring during the soaking process; then putting the soaked rubber particles into acetic acid for neutralization, and washing them with clean water; and obtaining modified rubber particles after drying.

[0016] In the above scheme, the rubber particles are soaked in a 35% sodium hydroxide solution for 3.5 hours, 4 hours or 4.5 hours.

[0017] In the above scheme, the modified polyacrylonitrile PAN fiber described in step S1 is a fiber surface roughened to increase the adhesion between the polyacrylonitrile PAN fiber and the cement-based slurry, form an interlaced network structure in the cement-based slurry, and improve the anti-cracking performance of the expansion joint concrete. The specific preparation method is as follows: select polyacrylonitrile PAN fiber with a length of 10-14 mm, heat a 40% sodium hydroxide aqueous solution to 55-60° C., add the polyacrylonitrile PAN fiber and soak it for 20-40 minutes, cool it to room temperature, wash it with clean water, and dry it to obtain the modified polyacrylonitrile PAN fiber with a rough surface, which enhances the water absorption of the fiber.

[0018] In the above scheme, the length of the polyacrylonitrile PAN fiber is 11 mm, 12 mm or 13 mm; the 40% sodium hydroxide aqueous solution is heated to 58° C., 60° C. or 62° C.; and the immersion time of the polyacrylonitrile PAN fiber is 25 min, 30 min or 35 min.

[0019] According to another aspect of the present disclosure, there is provided a bridge expansion joint anchorage zone concrete having high crack resistance prepared by the method described.

[0020] According to another aspect of the present disclosure, there is provided a bridge expansion joint anchorage zone concrete with high crack resistance prepared by the method, and its application in the fields of construction, transportation, bridges or roads.

[0021] The highly crack-resistant concrete for bridge expansion joint anchorage area provided by the present disclosure and its preparation method and application have the following beneficial effects compared with the prior art:

[0022] (1) The highly crack-resistant concrete for bridge expansion joint anchorage area provided by the present invention, as well as its preparation method and application, uses high-temperature calcined diatomaceous earth-rice husk ash as a highly active internal curing agent for concrete, modified rubber particles and modified PAN fibers, thereby greatly improving the mechanical properties, shrinkage properties and crack resistance of the highly crack-resistant concrete for expansion joint anchorage area, and effectively solving the problems of easy cracking, breakage and poor durability of the concrete for expansion joint anchorage area, thereby improving the performance of the concrete for expansion joint anchorage area, reducing the maintenance cost of the expansion joint anchorage area, and extending the full life cycle of the expansion joint anchorage area.

[0023] (2) The highly crack-resistant concrete for the anchor zone of a bridge expansion joint provided by the present invention, as well as its preparation method and application, adopts diatomaceous earth-rice husk ash calcined at high temperature as a highly active internal curing agent for concrete. Rice husk ash, as a highly active admixture, is mixed with diatomaceous earth and calcined at high temperature. The respective advantages of the two materials can be brought into play in concrete. The high activity of rice husk ash improves the compactness of the internal structure of the concrete in the anchor zone of the expansion joint and improves the durability of the concrete. The porous structure of the diatomaceous earth after calcination absorbs and returns water, thereby reducing the water loss caused by hydration reaction in the internal pores of the concrete structure, reducing the shrinkage deformation of the expansion joint concrete, and reducing the risk of cracking of the concrete in the anchor zone of the expansion joint.

[0024] (3) The highly crack-resistant concrete for the anchorage area of ​​bridge expansion joints provided by the present disclosure, as well as its preparation method and application, uses modified rubber particles. The modified rubber particles have a rough surface, which increases the bonding force with the cement matrix and the interface strength. The modified rubber particles are added to the expansion joint concrete as fine aggregate. Relying on the elasticity of the rubber particles themselves, the elastic deformation of the concrete is increased, which can buffer the vehicle load, absorb the impact energy received by the anchorage area of ​​the expansion joint, and reduce the risk of cracking and damage of the concrete in the anchorage area. At the same time, the rubber particles are solid waste, and the application of rubber particles to the expansion joint concrete also achieves the purpose of solid waste utilization, energy saving and environmental protection.

[0025] (4) The highly crack-resistant concrete for the anchor zone of a bridge expansion joint provided by the present invention, as well as its preparation method and application, uses modified PAN fibers, and roughens the surface of the PAN fibers to increase the adhesion between the PAN fibers and the cement-based slurry, thereby forming an interlaced network structure in the cement-based slurry and improving the crack resistance of the expansion joint concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The above contents and other objects, features and advantages of the present disclosure will become more apparent through the following description of the embodiments of the present disclosure with reference to the accompanying drawings, in which:

[0027] Figure 1 A flow chart of a method for preparing highly crack-resistant concrete in the anchorage area of ​​a bridge expansion joint according to an embodiment of the present disclosure is shown. DETAILED DESCRIPTION

[0028] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present disclosure. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present disclosure. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of the concepts of the present disclosure.

[0029] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.

[0030] All terms (including technical and scientific terms) used herein have the meanings commonly understood by those skilled in the art unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification and should not be interpreted in an idealized or overly rigid manner.

[0031] In order to solve the problems of cracking, damage and poor durability of concrete in the expansion joint anchorage area, improve the performance of concrete in the expansion joint anchorage area, reduce the maintenance cost of the expansion joint anchorage area, and extend the full life cycle of the expansion joint anchorage area, such as Figure 1 As shown, the present disclosure provides a method for preparing concrete in the anchoring area of ​​a bridge expansion joint with high crack resistance, comprising:

[0032] S1: weigh the raw materials according to the following weight parts: 650-660 parts of cement, 200-210 parts of fly ash, 100-110 parts of slag powder, 100-110 parts of high-activity internal curing agent, 500-550 parts of sand, 500-550 parts of stone, 18-20 parts of rubber powder, 50-60 parts of modified rubber particles, 1-1.2 parts of water reducing agent, 60-70 parts of steel fiber, 8-9 parts of modified polyacrylonitrile PAN fiber and 230-240 parts of water;

[0033] In this step, the high-activity internal curing agent adopts diatomaceous earth-rice husk ash after high-temperature calcination, wherein rice husk ash is a high-activity admixture, and after being mixed with diatomaceous earth and calcined at high temperature, the respective advantages of the two materials can be brought into play in concrete. The high activity of rice husk ash improves the compactness of the internal structure of concrete in the expansion joint anchoring area and improves the durability of concrete. The porous structure of diatomaceous earth after calcination absorbs and returns water, reduces the water loss caused by hydration reaction in the internal pores of the concrete structure, reduces the shrinkage deformation of the expansion joint concrete, and reduces the risk of cracking of the concrete in the expansion joint anchoring area.

[0034] Optionally, the highly active internal curing agent is prepared by the following method: crushing and grinding natural diatomaceous earth to a particle size range of 0.075-0.15 mm, calcining it at a high temperature of 800-820°C for 55-65 min, taking it out after calcination and directly placing it in a low temperature environment of -18--22°C for cooling for 50-70 min; then mixing the cooled diatomaceous earth and rice husk ash in a mass ratio of 3:1, stirring them at a high speed, calcining them at 600-620°C for 55-65 min, and restoring them to room temperature in a dry environment after calcination to obtain a highly active internal curing agent. Optionally, the high-temperature calcination time at 800-820°C is 58 min, 60 min or 62 min; the cooling in the low-temperature environment is cooling in a low-temperature environment of -18°C, -20°C or -22°C for 55 min, 60 min or 65 min; the high-temperature calcination time at 600-620°C is 58 min, 60 min or 62 min.

[0035] In this step, the modified rubber particles are prepared by the following method: selecting damaged rubber particles with a particle size of 1 to 3 mm, soaking the rubber particles in a 35% sodium hydroxide solution for 3.5 to 4.5 hours, and continuously stirring during the soaking process; then putting the soaked rubber particles into acetic acid for neutralization, and washing them with clean water; and drying them to obtain modified rubber particles. Optionally, the rubber particles are soaked in a 35% sodium hydroxide solution for 3.5 hours, 4 hours, or 4.5 hours.

[0036] In this step, the modified polyacrylonitrile PAN fiber is roughened on the surface of the polyacrylonitrile PAN fiber to increase the bonding strength between the polyacrylonitrile PAN fiber and the cement-based slurry, form an interlaced mesh structure in the cement-based slurry, and improve the anti-cracking performance of the expansion joint concrete. The specific preparation method is as follows: select polyacrylonitrile PAN fiber with a length of 10~14mm, heat a 40% sodium hydroxide aqueous solution to 55~60℃, add the polyacrylonitrile PAN fiber and soak it for 20~40min, cool it to room temperature and wash it with clean water, and dry it to obtain the modified polyacrylonitrile PAN fiber with a rough surface, which enhances the water absorption of the fiber. Optionally, the length of the polyacrylonitrile PAN fiber is 11mm, 12mm or 13mm; the 40% sodium hydroxide aqueous solution is heated to 58℃, 60℃ or 62℃; the soaking time of the polyacrylonitrile PAN fiber is 25min, 30min or 35min.

[0037] S2: Mixing and stirring cement, fly ash, slag powder, high-activity internal curing agent, sand, stone, rubber powder, modified rubber particles, water reducing agent and water to obtain a concrete mixture;

[0038] S3: adding steel fiber and modified polyacrylonitrile (PAN) fiber into the concrete mixture and continuing to stir evenly to obtain highly crack-resistant concrete for the anchorage area of ​​the bridge expansion joint.

[0039] Based on the above Figure 1 The method for preparing highly crack-resistant concrete for the anchorage area of ​​a bridge expansion joint shown in the figure is described in detail below in combination with Examples 1 to 3 and Comparative Examples 1 to 3, and the method for preparing highly crack-resistant concrete for the anchorage area of ​​a bridge expansion joint provided by the present invention is described in detail.

[0040] Embodiment 1:

[0041] The present embodiment includes the following components in parts by weight: 650 parts of cement, 205 parts of fly ash, 110 parts of slag powder, 110 parts of high-activity internal curing agent, 550 parts of sand, 500 parts of stone, 1.0 part of water reducer, 18 parts of rubber powder, 50 parts of modified rubber particles, 70 parts of steel fiber, 8 parts of modified PAN fiber, and 240 parts of water.

[0042] The cement, fly ash, slag powder, high-activity internal curing agent, sand, stone, rubber powder, modified rubber particles, water reducing agent and water in the above raw materials are mixed and stirred in proportion to form a concrete mixture; steel fiber and modified PAN fiber are added to the concrete mixture, and the mixture is continuously stirred to obtain a highly crack-resistant expansion joint concrete.

[0043] Embodiment 2:

[0044] The present embodiment includes the following components in parts by weight: 655 parts of cement, 205 parts of fly ash, 105 parts of slag powder, 105 parts of high-activity internal curing agent, 525 parts of sand, 525 parts of stone, 1.2 parts of water reducer, 19 parts of rubber powder, 55 parts of modified rubber particles, 60 parts of steel fiber, 9 parts of modified PAN fiber, and 230 parts of water.

[0045] The cement, fly ash, slag powder, high-activity internal curing agent, sand, stone, rubber powder, modified rubber particles, water reducing agent and water in the above raw materials are mixed and stirred in proportion to form a concrete mixture; steel fiber and modified PAN fiber are added to the concrete mixture, and the mixture is continuously stirred to obtain a highly crack-resistant expansion joint concrete.

[0046] Embodiment 3:

[0047] This embodiment includes the following components in parts by weight: 660 parts of cement, 210 parts of fly ash, 100 parts of slag powder, 100 parts of high-activity internal curing agent, 500 parts of sand, 550 parts of stone, 1.1 parts of water reducer, 20 parts of rubber powder, 60 parts of modified rubber particles, 65 parts of steel fiber, 8.5 parts of modified PAN fiber, and 235 parts of water.

[0048] The cement, fly ash, slag powder, high-activity internal curing agent, sand, stone, rubber powder, modified rubber particles, water reducing agent and water in the above raw materials are mixed and stirred in proportion to form a concrete mixture; steel fiber and modified PAN fiber are added to the concrete mixture, and the mixture is continuously stirred to obtain a highly crack-resistant expansion joint concrete.

[0049] Comparative Example 1:

[0050] This comparative example includes the following components in parts by weight: 650 parts of cement, 205 parts of fly ash, 110 parts of slag powder, 550 parts of sand, 500 parts of stone, 1.0 parts of water reducer, 18 parts of rubber powder, 70 parts of steel fiber, 8 parts of modified PAN fiber, and 240 parts of water. Compared with Examples 1 to 3 of the present disclosure, the high-activity internal curing agent and modified rubber particles are missing.

[0051] The cement, fly ash, slag powder, sand, stone, rubber powder, water reducing agent and water in the above raw materials are mixed and stirred in proportion to form a concrete mixture; the steel fiber and the modified PAN fiber are added to the concrete mixture, and the mixture is stirred evenly to obtain the expansion joint concrete.

[0052] Comparative Example 2:

[0053] This comparative example includes the following components in parts by weight: cement 655, fly ash 205, slag powder 105, high-activity internal curing agent 105, sand 525, stone 525, water reducer 1.2, rubber powder 19, steel fiber 60, water 230. Compared with Examples 1 to 3 of the present disclosure, the modified rubber particles and modified PAN fibers are missing.

[0054] The cement, fly ash, slag powder, high-activity internal curing agent, sand, stone, rubber powder, water reducing agent and water in the above raw materials are mixed and stirred in proportion to form a concrete mixture; the steel fiber is added to the concrete mixture, and the mixture is stirred evenly to obtain expansion joint concrete.

[0055] Comparative Example 3:

[0056] This comparative example includes the following components in parts by weight: cement 660, fly ash 210, slag powder 100, sand 500, stone 550, water reducer 1.1, rubber powder 20, modified rubber particles 60, steel fiber 65, water 235. Compared with Examples 1 to 3 of the present disclosure, the high-activity internal curing agent and modified PAN fiber are missing.

[0057] The cement, fly ash, slag powder, sand, stone, rubber powder, modified rubber particles, water reducing agent and water in the above raw materials are mixed and stirred in proportion to form a concrete mixture; the steel fiber is added to the concrete mixture, and the mixture is stirred evenly to obtain expansion joint concrete.

[0058] The mechanical properties, shrinkage properties and flat plate cracking tests were performed on Examples 1 to 3 and Comparative Examples 1 to 3, and the test results are shown in Table 1:

[0059]

[0060] Table 1

[0061] As can be seen from Table 1, the highly crack-resistant concrete in the anchorage area of ​​a bridge expansion joint provided by the present invention performs well in mechanical properties, shrinkage properties, and crack resistance, and can better solve the problems of easy cracking, breakage, and poor durability of the concrete in the anchorage area of ​​the expansion joint, thereby improving the performance of the concrete in the anchorage area of ​​the expansion joint, reducing the maintenance cost of the anchorage area of ​​the expansion joint, and extending the full life cycle of the anchorage area of ​​the expansion joint.

[0062] It can be seen that the preparation method of the highly crack-resistant concrete for the expansion joint anchor zone of a bridge provided by the present invention, by using diatomaceous earth-rice husk ash calcined at high temperature as a high-activity internal curing agent for concrete, modified rubber particles and modified PAN fibers, greatly improves the mechanical properties, shrinkage properties and crack resistance of the highly crack-resistant concrete for the expansion joint anchor zone, and better solves the problems of easy cracking, breakage and poor durability of the concrete in the expansion joint anchor zone, improves the performance of the concrete in the expansion joint anchor zone, reduces the maintenance cost of the expansion joint anchor zone, and extends the full life cycle of the expansion joint anchor zone.

[0063] Furthermore, based on the above-mentioned method for preparing highly crack-resistant concrete for the anchoring zone of a bridge expansion joint, the present disclosure also provides highly crack-resistant concrete for the anchoring zone of a bridge expansion joint prepared by the method, wherein the highly crack-resistant concrete for the anchoring zone of a bridge expansion joint has good mechanical properties, shrinkage properties and crack resistance, and better solves the problems of easy cracking, breakage and poor durability of the concrete in the anchoring zone of the expansion joint, improves the performance of the concrete in the anchoring zone of the expansion joint, reduces the maintenance cost of the anchoring zone of the expansion joint, and extends the full life cycle of the anchoring zone of the expansion joint.

[0064] Furthermore, based on the above-mentioned high crack resistance bridge expansion joint anchor area concrete and its preparation method, the present disclosure also provides a high crack resistance bridge expansion joint anchor area concrete prepared by the said method, which can be widely used in the fields of construction, transportation, bridges or roads, and can be widely used in lightweight concrete, concrete blocks, sewage treatment and other fields.

[0065] It will be appreciated by those skilled in the art that the features described in the various embodiments of the present disclosure may be combined and / or combined in a variety of ways, even if such combinations or combinations are not explicitly described in the present disclosure. In particular, without departing from the spirit and teachings of the present disclosure, the features described in the various embodiments of the present disclosure may be combined and / or combined in a variety of ways. All of these combinations and / or combinations fall within the scope of the present disclosure.

[0066] The embodiments of the present disclosure are described above. However, these embodiments are only for illustrative purposes and are not intended to limit the scope of the present disclosure. Although the embodiments are described above, this does not mean that the measures in the various embodiments cannot be used in combination to advantage. Without departing from the scope of the present disclosure, those skilled in the art may make a variety of substitutions and modifications, which should all fall within the scope of the present disclosure.

Claims

1. A method for preparing highly crack-resistant concrete for bridge expansion joint anchorage areas, characterized in that: include: S1: weigh the raw materials according to the following weight parts: 650-660 parts of cement, 200-210 parts of fly ash, 100-110 parts of slag powder, 100-110 parts of high-activity internal curing agent, 500-550 parts of sand, 500-550 parts of stone, 18-20 parts of rubber powder, 50-60 parts of modified rubber particles, 1-1.2 parts of water reducing agent, 60-70 parts of steel fiber, 8-9 parts of modified polyacrylonitrile PAN fiber and 230-240 parts of water; S2: Mixing and stirring cement, fly ash, slag powder, high-activity internal curing agent, sand, stone, rubber powder, modified rubber particles, water reducing agent and water to obtain a concrete mixture; S3: adding steel fiber and modified polyacrylonitrile (PAN) fiber into the concrete mixture and continuing to stir evenly to obtain highly crack-resistant concrete for the anchorage area of ​​the bridge expansion joint.

2. The method for preparing the highly crack-resistant bridge expansion joint anchorage zone concrete according to claim 1, characterized in that: The high-activity internal curing agent described in step S1 adopts diatomaceous earth-rice husk ash after high-temperature calcination, wherein rice husk ash is a high-activity admixture. After being mixed with diatomaceous earth and calcined at high temperature, the respective advantages of the two materials can be brought into play in concrete. The high activity of rice husk ash improves the compactness of the internal structure of concrete in the expansion joint anchoring area and improves the durability of concrete. The porous structure of diatomaceous earth after calcination absorbs and returns water, reduces the water loss caused by hydration reaction in the internal pores of the concrete structure, reduces the shrinkage deformation of the expansion joint concrete, and reduces the risk of cracking of the concrete in the expansion joint anchoring area.

3. The method for preparing the highly crack-resistant bridge expansion joint anchorage zone concrete according to claim 2, characterized in that: The highly active internal curing agent described in step S1 is prepared by the following method: The natural diatomaceous earth is crushed and ground into a particle size range of 0.075-0.15 mm, and calcined at 800-820°C for 55-65 min. After calcination, it is taken out and directly placed in a low temperature environment of -18--22°C for cooling for 50-70 min. Then, the cooled diatomaceous earth and rice husk ash are mixed in a mass ratio of 3:1, and stirred at a high speed, calcined at 600-620°C for 55-65 min, and restored to room temperature in a dry environment after calcination to obtain a high-activity internal curing agent.

4. The method for preparing the highly crack-resistant bridge expansion joint anchorage zone concrete according to claim 3, characterized in that: The high temperature calcination time of 800-820°C is 58min, 60min or 62min; The cooling in the low temperature environment is cooling in a low temperature environment of -18°C, -20°C or -22°C for 55min, 60min or 65min; The high temperature calcination time at 600-620° C. is 58 min, 60 min or 62 min.

5. The method for preparing the highly crack-resistant bridge expansion joint anchorage zone concrete according to claim 1, characterized in that: The modified rubber particles described in step S1 are prepared by the following method: Select broken rubber particles with a particle size of 1-3 mm, soak the rubber particles in a 35% sodium hydroxide solution for 3.5-4.5 hours, and continuously stir the rubber particles during the soaking process; then put the soaked rubber particles into acetic acid for neutralization, and wash them with clean water; after drying, obtain modified rubber particles.

6. The method for preparing the highly crack-resistant concrete for the bridge expansion joint anchorage zone according to claim 5, characterized in that: The rubber particles are soaked in a 35% sodium hydroxide solution for 3.5 hours, 4 hours or 4.5 hours.

7. The method for preparing the highly crack-resistant concrete for bridge expansion joint anchorage area according to claim 1, characterized in that: The modified polyacrylonitrile (PAN) fiber described in step S1 is obtained by roughening the surface of the polyacrylonitrile (PAN) fiber to increase the bonding strength between the polyacrylonitrile (PAN) fiber and the cement-based slurry, forming an interlaced mesh structure in the cement-based slurry, and improving the crack resistance of the expansion joint concrete. The specific preparation method is as follows: Select polyacrylonitrile (PAN) fibers with a length of 10-14 mm, heat a 40% sodium hydroxide aqueous solution to 55-60°C, add the polyacrylonitrile (PAN) fibers and soak them for 20-40 minutes. After cooling to room temperature, wash them with clean water and dry them to obtain modified polyacrylonitrile (PAN) fibers with a rough surface, which enhances the water absorption of the fibers.

8. The method for preparing the highly crack-resistant concrete for the bridge expansion joint anchorage zone according to claim 7, characterized in that: The length of the polyacrylonitrile (PAN) fiber is 11 mm, 12 mm or 13 mm; The 40% sodium hydroxide aqueous solution is heated to 58° C., 60° C. or 62° C.; The immersion time of the polyacrylonitrile (PAN) fiber is 25 minutes, 30 minutes or 35 minutes.

9. A bridge expansion joint anchorage zone concrete with high crack resistance prepared by the method according to any one of claims 1 to 8.

10. Use of a bridge expansion joint anchorage zone concrete with high crack resistance prepared by the method according to any one of claims 1 to 8 in the fields of construction, transportation, bridges or roads.